Highly educated patients have lower dental compliance during the COVID-19 pandemic: an observational study - Yu-Hsiang Chou; Ying-Chu Lin; Mei-Hsuan Lee; Yu-Ting Huang; Pei-Feng Liu; Chung-Lin Huang; Kai-Fang Hu (BMC Oral Health, 2022)
Abstract Background The outbreak of coronavirus disease 2019 (COVID-19) is rapidly changed medical habits, and dental clinics have been forced to adapt. This study explored the pandemic-induced changes in patient utilization of dental services to assist practitioners in responding efficiently to similar public crises as references in the future. Methods We retrospectively analyzed the correlation between patient profiles and dental visits attendance within 2 months before and during the outbreak. Results A total of 332 patients, 210 women and 122 men (total number of visits: 1068) were enrolled in this study. A significantly lower attendance rate was noted during the COVID-19 period (70.3%) than prior to the pandemic (83.4%). The rate of return visits for patients with a high education level during the COVID-19 period was significantly reduced from 96.5 to 93.1%. In addition, the number of days between two visits significantly increased during the pandemic. Conclusions Our results indicate that, during the pandemic period, the attendance rates of return dental appointments decreased, and the rate of missed appointments for patients with a high educational levels was higher than that of patients with a low educational level. Clinical relevance Preventive management of these patients who are easy to miss dental appointments may enable more effective use of medical resources.